Metrics for implosion performance with enhanced energy coupling on NIF. (14th October 2021) - Zylstra, A.B.; Hurricane, O.A.; Callahan, D.A.; Kritcher, A.L.; Landen, O.L.; Lindl, J.; Pak, A.; Patel, P.; Ralph, J.E.; Ross, J.S.; Young, C.V.
Abstract: In 2017–2018, record fusion yields on NIF were produced with designs that utilized high-density-carbon capsules and low-gas-fill hohlraums. Subsequently, a strategy was pursued to increase the capsule size and thus the energy absorbed by the capsule, with the latter occasionally used as a metric for these campaigns presuming that subsequent energy transfer would lead to a concomitant increase in hot-spot energy. Here we show that improved performance in recent experiments was not solely enabled by the capsule absorbed energy, which is a poor metric as it is weakly correlated with implosion performance ( r ∼ 0.3). Metrics that incorporate additional information about the implosion physics or degradation mechanisms are significantly better for understanding the performance of these shots. These metrics, such as the hot-spot energy multiplied by pressure squared or the experimental ignition threshold factor (ITFX), should be used for guiding the experimental program on NIF for further improvements as they exhibit much stronger correlations with performance ( r ∼ 0.8–0.9).